Analysis of Bacterial Diversity In Temple Bricks Using Phenetic Numeric Taxonomy Method - Alifia, Luluk; Zulaika, Enny; Soeprijanto, Soeprijanto (Jurnal Biodjati, 2024)
Temple bricks-based constructions are known to often face various challenges, including physical, chemical, and biological weathering. Previous studies identified various biological factors contributing to brick weathering including exudate produced by microorganisms, such as bacteria. In addition, bacteria often live synergistically and antagonistically with other species, exhibiting diverse morphological and physiological traits (bacterial diversity). Various methods have been developed to explore bacterial diversity, with phenetic numerical taxonomy being the most popular. Therefore, this study aims to determine bacterial diversity on the surfaces of temple bricks using phenetic numerical taxonomy method. Bacterial isolation was carried out aseptically, followed by labeling and transferring the isolate to the laboratory for further tests. The tests carried out included morphological characterization, biochemical assays, physiological reactions, and potential enzymatic activities. Subsequently, dendrogram was constructed using MVSP (Multi-Variate Statistical Package) software with isolated grouping based on the Unweighted Pair Group Method Averages (UPGMA) algorithm. The similarity between isolates was analyzed using the Simple Matching Coefficient (SSM) similarity value. The dendrogram analysis revealed the presence of 3 clusters namely A (4 isolates), B (1 isolate), and C (2 isolates), with a similarity index of 0,543 to 0,857. Clusters A, B, and C had a similarity index of ≤0.700, indicating the occurrence of distinct species in each cluster. Based on the profile-matching results of key characters, the 7 bacterial isolates were identified as belonging to the genera Bacillus, Corynebacterium, and Mycobacterium.